The effects of quality grade, postmortem aging, and blade tenderization on Warner-Bratzler shear force and cookery traits of biceps femoris steaks - Andrews, B.S.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used 108 top sirloin butts to determine the influence of quality grades, postmortem aging periods, and blade tenderization passes on percentages of thawing and cooking losses and Warner-Bratzler shear (WBS) force of biceps femoris muscles. Top sirloin butts that qualified for either USDA Select (SEL, n=36), USDA Choice (CHO, n=36), or Certified Angus Beef™ Program (CAB, n=36), were aged for 14 or 21 days and blade tenderized zero (0X), one (1X), or two (2X) times. Steaks with higher quality grades (CHO and CAB) aged for 21 days had lower thawing losses than steaks aged 14 days and than SEL steaks aged for 21 days. Steaks aged for 14 days and not blade tenderized (0X) had higher thawing losses than steaks aged for longer periods (21 days) and tenderized 0X, 1X, and 2X. Lower quality grade steaks (SEL) blade-tenderized 2X had longer cooking times than other quality grade×blade tenderization treatments. More blade tenderization passes (1X and 2X) for higher quality grades (CHO and CAB) appear to lower WBS values. The most tender treatments were CHO steaks blade tenderized 2X and CAB steaks blade tenderized 1X and 2X. Biceps femoris tenderness was inconsistent among all treatments, although aging, blade tenderization, and higher quality grades reduce variation. For reliable, acceptable quality this muscle should not be included in top sirloin butt steaks.
Keywords: Beef; Quality; Blade tenderization; Postmortem aging; Biceps femoris; Tenderness